La Ciruela: Culture and Resistance in the Chilean Military Dictatorship - de Moura Cavalcante de Melo, Ana Amélia; de la Cuadra Arancibia, Fernando (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes the material published in the Chilean magazine La Ciruela, seeking to identify the meanings of left-wing student resistance in Chile under dictator Augusto Pinochet, as well as to better understand the notion of "cultural apagón". La Ciruela (The Plum) was produced and published by the Agrupación Cultural Universitaria (ACU), a student organization at the University of Chile, which managed to maintain student organization through cultural activities and facilitated the gradual reorganization of left-wing activism on campus. The magazine circulated from 1979 to 1982, always marked by irreverence, humor, and parody, constantly challenging the dictatorship with its cartoons and articles denouncing censorship, repression, and persecution of students.
Keywords: La Ciruela; Agrupación Cultural Universitaria; Chilean Dictatorship; University Student Movement; Student Press